HTML5 for dummies eLearning kit - Boumphrey, Frank (Wiley, 2012)
Helping self-directed learners of all levels learn HTML5 If you want to develop and structure pages for the web, HTML5 is one of the tools you need. This invaluable eLearning kit steps you through learning HTML5, CSS3, and JavaScript.